First record of the Vulnerable Malayan Flat-shelled Turtle, Notochelys platynota (Gray 1834) (Reptilia, Testudines, Geoemydidae), in Belitung, Indonesia - Veryl Hasan; Josie South (Check List, 2023)
The Malayan Flat-shelled Turtle, Notochelys platynota (Gray 1834), is a freshwater turtle endemic across Southeast Asia and is categorized as Vulnerable according to the IUCN Red list. We report the first record of this species from Belitung, a remote Island in Indonesia, based on photographs. The new record is approximately 150 km to the east of the nearest locality on Bangka Island, Indonesia. This species was obtained in upstream, slow-flowing waters in forested hills 75 m above sea level.